Alkyne dimerization-hydroarylation to form pentasubstituted 1,3-dienes via binuclear nickel catalysis - Ke Chen; Hongdan Zhu; Shuxin Jiang; Kuiling Ding; Qian Peng; Xiaoming Wang (Nature Communications)
Abstract Mono-metallic catalysts dominate in homogeneous catalysis, wherein all the element steps generally occur on one metal site. Inspired from bimetallic active sites in both enzymes and heterogeneous catalysts, the development of binuclear catalysis can offer the potential to induce novel intermediates, reactivity, and selectivity. Metal-catalyzed hydroarylation of alkynes generally leads to one alkyne incorporated products and alkyne dimerization-hydrocarbofunctionalization is rather challenging via conventional mono-metallic intermediates. Herein, a highly selective dimerization-hydrocarbofunctionalization of internal alkynes is achieved via dinickel catalysis, leading to the formation of synthetically challenging pentasubstituted 1,3-dienes. Mechanistic studies suggest that each Ni site can promote distinct elementary steps of two alkynes to generate a di-vinyl di-Ni intermediate. Such a mode of “binuclear convergent catalysis” is fundamentally different from the traditional mono-metallic catalysis and may provide new understanding on binuclear synergistic effects at atomic and molecular level.